Proactive Vs Reactive Therapeutic Drug Monitoring of Infliximab in Crohn's Disease: A Cost-Effectiveness Analysis in a Simulated Cohort. Issue 1 (10th June 2019) - Negoescu, Diana M; Enns, Eva A; Swanhorst, Brooke; Baumgartner, Bonnie; Campbell, James P; Osterman, Mark T; Papamichael, Konstantinos; Cheifetz, Adam S; Vaughn, Byron P
Abstract : Proactive therapeutic drug monitoring of infliximab is a marginally cost-effective strategy for Crohn's disease, whereas reactive therapeutic drug monitoring is cost-effective. As the cost of infliximab decreases, a proactive strategy of dosing infliximab becomes more cost-effective. Abstract: Background: Therapeutic drug monitoring (TDM) is increasingly performed for Infliximab (IFX) in patients with Crohn's disease (CD). Reactive TDM is a cost-effective strategy to empiric IFX dose escalation. The cost-effectiveness of proactive TDM is unknown. The aim of this study is to assess the cost-effectiveness of proactive vs reactive TDM in a simulated population of CD patients on IFX. Methods: We developed a stochastic simulation model of CD patients on IFX and evaluated the expected health costs and outcomes of a proactive TDM strategy compared with a reactive strategy. The proactive strategy measured IFX concentration and antibody status every 6 months, or at the time of a flare, and dosed IFX to a therapeutic window. The reactive strategy only did so at the time of a flare. Results: The proactive strategy led to fewer flares than the reactive strategy. More patients stayed on IFX in the proactive vs reactive strategy (63.4% vs 58.8% at year 5). From a health sector perspective, a proactive strategy was marginally cost-effective compared with a reactive strategy (incremental cost-effectiveness ratio of $146, 494 per quality-adjusted life year), assuming a 40% of the wholesale price of IFX. The results were most sensitive to risk of flaring with a low IFX concentration and the cost of IFX. Conclusions: Assuming 40% of the average wholesale acquisition cost of biologic therapies, proactive TDM for IFX is marginally cost-effective compared with a reactive TDM strategy. As the cost of infliximab decreases, a proactive monitoring strategy is more cost-effective.